Safety of undergraduate nursing students during their clinical education: A review of the literature. - I Asfour, Hayam; Ramaiah, Pushpamala; Nomani, Ibtesam; A Abbakr, Ibrahim; E Ahmed, Esraa; A Elfaki, Badria; E Mustafa, Hassanat; M Lindsay, Grace; M Khamis, Hamdia; Monica V, Agnes (Journal of Neonatal Surgery, 2025)
Background: Areas of clinical training such as hospitals and community health centers are difficult to control and considered sources of risks that threaten the safety of the students which affects their success and fulfilling the goals of nursing education and may have long-term effects on their quality of life. Aim: This review aimed to critically review the scientific evidence related to students’ risk perception regarding the effect of clinical education on their safety. Methods: A systematic search was carried out for quantitative studies published between January 2010 and April 2023 to investigate undergraduate nursing students’ perceptions regarding the effect of clinical education on their safety. Six studies were identified to meet the aim of this review based on the titles and abstracts. Results: The total score of the nursing students' occupational risk perception scale was high in 3 studies. The highest nursing students' risk perception scale was psychological and ergonomic, followed by physical and clinical environment risks. Several factors were identified to affect students' perception of risks during their clinical education: age, gender, students’ level of anxiety, the clinical environment, and the level of students’ knowledge about safety in the clinical environment. Conclusion: The findings of this review show worthy data for clinical educators regarding the students’ perception of the effect of clinical training on their personal safety. Moreover, this review highlights certain points; there are inadequate studies investigating the concepts of risks and safety from undergraduate nursing students’ perceptions. Future studies should pay attention to the perceptions of students with different levels of study and educational backgrounds and in different cultures and countries.